2011
DOI: 10.1002/j.2050-0416.2011.tb00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Current Developments in Malting and Brewing Trials with Sorghum in Nigeria: A Review

Abstract: Initially, large‐scale lager beer brewing with sorghum malts proved highly intractable due to a number of biochemical problems including: high malting losses estimated at 10–30% as against 8–10% for barley; high gelatinisation temperatures which limited starch solubilisation/ hydrolysis by the amylolytic enzymes during mashing; low extract yield/low diastatic power (DP) due to inadequate hydrolytic enzyme activities especially β‐amylase; low free α‐amino nitrogen (FAN) due to inadequate proteolysis limiting ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 36 publications
(66 reference statements)
1
23
2
2
Order By: Relevance
“…Glennie‐Holmes also refers to CWE as extracts formed in malts when enzyme activities have been inhibited. Values for CWE obtained here do not differ much from those previously reported for some species of sorghum , but they are slightly lower than those reported by Ogu et al . .…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Glennie‐Holmes also refers to CWE as extracts formed in malts when enzyme activities have been inhibited. Values for CWE obtained here do not differ much from those previously reported for some species of sorghum , but they are slightly lower than those reported by Ogu et al . .…”
Section: Discussioncontrasting
confidence: 81%
“…One key consideration among grains is size: bigger grains or kernels are often preferred because they contain proportionately less husk and therefore a higher starch content than smaller ones . The largest grains were SK5912 and KSV 8, which have been proven to have other important germinative and grain qualities in abundance . Indeed these two sorghum varieties, together with the smaller‐sized ICSV 400, have in several previous studies carried out in our laboratory shown tremendous proficiency in malting and brewery‐related capacities .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These results are similar to observed ethanol concentration of 379 L/t for KSV3 substrate reported in this study. However, previous studies have reported a favourable ethanol yield of 460-490 L/t with clean, sound and malted sorghum grains [8,[34][35][36][37], which are higher values than those reported here for de-husked and un-malted KSV8 sorghum grain (421 L/t).…”
Section: Conflict Of Interestcontrasting
confidence: 79%
“…These structural and NSPs are linear homopolymers of β ‐ d ‐glucopyranosyl residues linked mostly via two or three consecutive β ‐ linkages that are separated by a single β ‐ linkage . The β ‐glucans have been associated with increased wort viscosity, poor filtration performance, impaired pumping, reduced extract yield and gelatinous precipitates in matured beer, resulting in chill haze and poor shelf .…”
Section: Introductionmentioning
confidence: 99%